2021
DOI: 10.3390/nu13114024
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Pre-Operative Protein Caloric Restriction in Elective Vascular Surgery Patients: A Randomized Clinical Trial

Abstract: (1) Background: Vascular surgery operations are hampered by high failure rates and frequent occurrence of peri-operative cardiovascular complications. In pre-clinical studies, pre-operative restriction of proteins and/or calories (PCR) has been shown to limit ischemia-reperfusion damage, slow intimal hyperplasia, and improve metabolic fitness. However, whether these dietary regimens are feasible and safe in the vascular surgery patient population remains unknown. (2) Methods: We performed a randomized controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Therefore, the diet may have a systemic immunomodulatory role despite our findings of a microbial imbalance. Kip et al subsequently tested the liquid diet on eight vascular surgery patients, with 100% compliance [ 19 ]. Pre-operative improvements in insulin sensitivity were noted, with no differences in surgical outcomes compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the diet may have a systemic immunomodulatory role despite our findings of a microbial imbalance. Kip et al subsequently tested the liquid diet on eight vascular surgery patients, with 100% compliance [ 19 ]. Pre-operative improvements in insulin sensitivity were noted, with no differences in surgical outcomes compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The selected diet was a 4-day calorie- and protein-restricted regimen followed by a return to an individual’s typical diet post-intervention. Preliminary findings have demonstrated the safety and feasibility of the diet [ 19 , 20 ]. The study was approved by the Institutional Review Board at the University of Florida.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Broadly, attenuation of proinflammatory signaling and production of anti-inflammatory chemokines are proposed mechanisms for its benefits [ 1 , 4 , 5 , 6 ]. Multiple, small, randomized controlled trials have demonstrated StDR safety and feasibility, yet mechanistic insights into its modulation of the human immune system remain limited [ 7 , 8 , 9 ]. The gut microbiome influences systemic immunity, and its modification represents an important area for translational therapeutic development [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%